(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In dialogue with the critique of democratic citizenship and a life without any, the following analysis aims to explore the spaces between nationality and the deprivation of - the legal invisibility and the de facto statelessness caused by the dichotomy of modern citizenship and the severity of purchasing one. Citizenship is a legal link between the persons and the states and does not indicate the ethnic origin of the persons, yet, a vast percentage of stateless persons count ethnic minorities. Legal neglect and institutional coordinative incoherence are an impediment of that link inevitably ensuing statelessness. Stateless individuals are the most vulnerable de jure persons in society. Their access to the array of fundamental rights is greatly restricted citizenship is, in practice, the passport to obtaining human rights. The continuing existence of the lack of citizenship of all, reveals the legal inefficiency of the much upgraded Rousseauian social contract. This paper will expose the national legislations alignment with international protection framework and will evaluate the efficiency of past and current practices, while identifying the dire obstacles and their potential to be transformed into safeguards in the emerging democratic state, a post-Yugoslav country of North Macedonia.